Ensino jurídico brasileiro e sociobiodiversidade: a possível e necessária construção de um cenário polifônico - Seeger, Luana da Silva (2019)
Through a hundred ninety-two years of history of legal education in Brazil we can see that we still follow a model of formation very close to the one that appeared in 1827. This happens because, in spite of the fact that we can observe many advances in curriculum changes and even epistemological, we go on reproducing the patriarchal, capitalist, colonial logic of domination and exploitation of nature, not human women and animals, about everything. Legal education continues contenting itself with the mere reproduction of dogmatic, from a speech of disguised power of neutrality. The dominating epistemological paradigm is identified as the strongest resistance to changes in Brazilian legal education being considered insufficient to give account of the formation of jurists compromised with biodiversity partnership. This, in its turn, is conceived as biological and cultural diversity existent in the world encompassing, most of all, the relation between humans and environment, among traditional knowledge, culture, life forms and relations of gender. We can see, however, that the paradigm that puts law and legal education in crisis, which is the dominating epistemological paradigm, is the same that subalterns biodiversity partnership for it considers as valid knowledge only what comes from the white man, hetero normative, cis, middle class, universalizing identities and marginalizing all that doesn’t fit in the referred pattern, according to the perspective of colonial knowledge. Regarding to this, a new epistemological paradigm needs to emerge so that the voices of biodiversity can be heard. Legal education, therefore, as an assumption of jurists formation which play an important role promoting the guarantee of rights to social biodiversity subaltern groups-must adopt a transdisciplinary perspective, in which there is no hierarchy of knowledge and fragmentation between humans and nature. This teaching is possible from the perspective of polyphony, which is the harmony of diverse voices of biodiversity co-existing. Thus, we give as an alternative to epistemological crisis that plagues legal education the possibility of constructing a polyphonic scenery from epistemological polyphony.